"Sie können versichert sein, dass wir das ändern werden". Kommunikativ-kontrastive Studie zu den Verben des "versicherns" im Deutschen und im Polnischen = "Może być pan pewien, że to zmienimy". Studium komunikatywno-kontrastywne czasowników zapewniania w języku niemieckim i polskim = "You can be sure we`ll change this". A communicative-contrastive study of the verbs of assurance in German and Polish - Laskowski, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper the communicative capacity of the verbs of assurance in German and Polish are compared and critically evaluated. Particular emphasis is placed on the communicative role and occurrence of the investigated verbs because the illocutionary role played a particular verb only in the particular communicative situation often arises from the context.
Keywords: akt mowy; czasownik performatywny; ekwiwalent; komunikacja; zapewnienie; assurance; communication; equivalent; performative verb; pragmatic function; speech act